2016
DOI: 10.1097/sla.0000000000001857
|View full text |Cite
|
Sign up to set email alerts
|

Can Sleeve Gastrectomy “Cure” Diabetes? Long-term Metabolic Effects of Sleeve Gastrectomy in Patients With Type 2 Diabetes

Abstract: LSG can significantly improve cardiometabolic risk factors including glycemic status in T2DM. Long-term complete remission and "cure" of T2DM, however, occur infrequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(42 citation statements)
references
References 41 publications
4
36
0
2
Order By: Relevance
“…Despite that there were no cases of complete remission of diabetes. Similar results and very rare diabetes remission was presented by Aminian (19).…”
Section: Discussionsupporting
confidence: 76%
“…Despite that there were no cases of complete remission of diabetes. Similar results and very rare diabetes remission was presented by Aminian (19).…”
Section: Discussionsupporting
confidence: 76%
“…In another study with a 10 year follow-up period, about half of the patients with VSG suffered from significant weight regain and many of these were converted to RYGB after only about 3 years [17]. Furthermore, in a five year follow-up study, long-term relapse after initial remission of type 2 diabetes occurred in over 40% of patients [31]. …”
Section: Discussionmentioning
confidence: 99%
“…The improvement of T2DM occurred soon after surgery, even without significant weight loss yet being achieved, and this fact could be attributed to hormonal changes, such as increased GLP-1 secretion or decreased ghrelin[6]. The long-term effects of LSG on T2DM evolution are under continuous evaluation, and Aminian et al[42] recently reported a 44% of long-term relapse of T2DM after initial remission and continuous complete remission for ≥ 5 years (“cure”) was achieved in only 3% of the patients. LSG and RYGB showed comparable remission rates of T2DM in a long-term observational study[18], but a meta-analysis including 6526 patients confirmed that RYGB achieved a higher diabetes remission rate (HR = 1.49, 95%CI: 1.04-2.12)[16].…”
Section: Discussionmentioning
confidence: 99%